Subcritical Phase Separation and Occurrence of Deep-Seated Brines at the NW Caldera Vent Field, Brothers Volcano: Evidence from Fluid Inclusions in Hydrothermal Precipitates. (16th September 2020) - Diehl, Alexander; de Ronde, Cornel E. J.; Bach, Wolfgang
Abstract : The northwestern caldera wall of Brothers volcano in the southern Kermadec arc features several clusters of hydrothermal venting in a large area that extends from near the caldera floor ( 1700 mbsl) almost up to the crater rim ( 1300 mbsl). Abundant black smoker-type hydrothermal chimneys and exposed stockwork mineralization in this area provide an excellent archive of hydrothermal processes that form seafloor massive sulfide deposits. Using sulfate precipitates from chimneys and stockwork recently recovered by remotely operated vehicles, we conducted fluid inclusion microthermometry and Sr isotope studies to determine the role of phase separation and mixing between vent fluid and seawater. The variability in the vast majority of fluid inclusion salinities (i.e., 0.1–5.25 wt.% NaCl eq.) and entrapment temperatures of up to 346°C are indicative of phase-separated hydrothermal fluids. Large salinity variations in samples with entrapment temperatures mostly below the boiling temperature for the sample's depth show that the majority of fluids ascending below the NW Caldera are phase separating in the subsurface and cooling, prior to discharge. In several samples, entrapment temperatures of over 343°C suggest that phase-separating fluids have at least sporadically exited the seafloor at the NW Caldera site. Isobaric-isenthalpic mixing trends between coexisting phase-separated vapors and brines with seawater are consistent with phase-separated fluids at near-seafloor pressures of 170 bar and suggest that the vast majority of the ascending fluids continue to phase separate to within tens to hundreds of meters below seafloor prior to mixing with seawater. A small subset of the most saline fluid inclusions (up to 18.6 wt.% NaCl eq.) is unlikely formed by near-seafloor phase separation and is considered to be produced either by supercritical phase separation or by the contribution of a magmatic brine from near the magmatic-hydrothermal interface. 87 Sr/ 86 Sr values of sulfate samples range from 0.7049 (i.e., near hydrothermal end-member) to 0.7090 (i.e., near seawater) and show that the crystals grew from vapor- and brine-derived fluids in a hydrothermally dominated mixing regime. Our work provides new insights into mineral growth conditions, mixing regimes, and in particular, the extent and character of subseafloor phase separation during the formation of hydrothermal vents and their underlying stockwork in seawater-dominated, arc-related hydrothermal systems.